PECTIN EXTRACTION AND CHARACTERIZATION FROM LOCAL WHITE PUMPKIN (LAGENARIA SICERARIA) - Ezzalddin, Sawen Manaf; Younis, Bawer J; Taha, Safea Sabir; Essa, Zeen T (Science Journal of University of Zakho, 2024)
Pectin, a naturally occurring heteropolysaccharide, has in recent years grown increasingly in importance. In this present study, white pumpkin or bottle gourd was chosen as a representative of the Cucurbitaceae family to extract powder pectin. At initial and final times, treatment (T1) and treatment (T2), the amount of pectin in calcium pectate in fresh pumpkin ranges from 3.7% to 5.8%. Standardized water bath heating was used to extract pectin from white pumpkins by boiling the fruit at atmospheric pressure for five minutes at 95 oC. Distilled water was also tested for pectin isolation from white pumpkins as an extraction solvent. The weight increased by 844.98% at T1 and decreased to 675.67% at T6, following which was precipitation with 95% ethanol yielding maximum on the above during the extraction of pectin by water bath at varied period durations. Finally, the degree of esterification was the rate 68.76% at T1 to 59.87% at T6, with the methoxyl content having a value 9.45% at T1 to 6.82% at T6 and the anhydrouronic acid content (AUA%) being 76.66% at T1 to 64.77% at T6. Moisture, equivalent weight, degree of esterification, and methoxyl concentration all reduced as extraction time increased. However, many indicators, like ash content, acetyl value, and jelly grade, exhibited an early rise in value that later declined as extraction time increased. Thus, the optimal method for pectin isolation involves boiling the pumpkin in water at atmospheric pressure for 5 to 30 minutes. In addition, among different times of extraction pectin that was obtained from 30 minutes had the highest lightness 82.07 while the lowest redness 2.03 and yellowness 5.14 of pectin was recorded at this time. This pectin met the criteria for food additive use, indicating its potential as a commercially viable alternative source.